The Effect of Time Constraint on Student Reading Comprehension Test Performance in Narrative Text - Martina, Feny; Syafryadin, Syafryadin; Rakhmanina, Lisa; Juwita, Sisma (JOLLT Journal of Languages and Language Teaching, 2020)
The objective of this study was to know whether there is any effect between the time constraints of students when doing exams using (extended time) with students who take exams using (non-extended time). The sample used in this study amounted to 60 grade 11 students in SMA 03 Kaur. The method used in this research was the quantitative method and uses ex post facto design. In collecting data the author gives multiple-choice exam questions consisting of 50 questions, these are questions in the form of narrative texts. In analyzing the data, the authors used the Mann Whitney U-Test in SPSS 16.0. The results of this study indicate that the influence of time constraints on student examinations using extended time.Â 